Produção de mudas de espécies ornamentais em substratos a base de resíduos agroindustriais e agropecuários - Araújo, Daniel Barbosa (2010)
Among the main technologies used in seedling production, stand out from the substrate type and volume of container. Currently the use of residues in a substrate constitutes a form of recycling these materials. The im of this study was to test eleven substrates and two types of containers in seedling production of Tagetes patula, Vinca and ornamental pepper. The substrates were formulated with compost CEASA waste + cattle anure (compound 01), CEASA waste + poultry manure litter (compound 02), bagasse-cane + cattle manure (compound 03), sugarcane bagasse sugar + poultry manure litter (compound 04), shell powder, coconut green and carnauba. The experiment was conducted in greenhouse and substrates were: S1: 01 + composite powder of green coconut + bagan (1:1:1, v / v) S2: 01 + consists of coconut powder (1:2 , v / v), S3: 01 + compound carnauba (1:2, v / v) S4: 02 + composite powder + coconut bagan (1:1:1, v / v) S5: compound 02 + coconut powder (1:2, v / v) S6: 02 + compound carnauba (1:2, v / v), S7: 03 + consists of coconut powder (1:1, v / v) S8: composed 2003 + carnauba (1:1, v / v) S9: + 04 composed of coconut powder (1:1, v / v) S10: composed 2004 + carnauba (1 : 1, v / v) and S11: commercial substrate. The containers used were plastic trays with 162 (30ml/célula) and 200 cells (18ml/célula) respectively. In general, the best results amoung the cultures studied were observed in the substrates formulated with waxpalm with any of the compounds used. The trays with cells of 18 ml produced seedlings of Tagetes Patula in quality, unlike the Vinca seedlings where found the best results in the volume of 30ml, and the ornamental pepper plants did not observe influence of the volume of container.